Food security among dryland pastoralists and agropastoralists: The climate, land-use change, and population dynamics nexus. (December 2022) - Stavi, Ilan; Roque de Pinho, Joana; Paschalidou, Anastasia K; Adamo, Susana B; Galvin, Kathleen; de Sherbinin, Alex; Even, Trevor; Heaviside, Clare; van der Geest, Kees
During the last decades, pastoralist, and agropastoralist populations of the world's drylands have become exceedingly vulnerable to regional and global changes. Specifically, exacerbated stressors imposed on these populations have adversely affected their food security status, causing humanitarian emergencies and catastrophes. Of these stressors, climate variability and change, land-use and management practices, and dynamics of human demography are of a special importance. These factors affect all four pillars of food security, namely, food availability, access to food, food utilization, and food stability. The objective of this study was to critically review relevant literature to assess the complex web of interrelations and feedbacks that affect these factors. The increasing pressures on the world's drylands necessitate a comprehensive analysis to advise policy makers regarding the complexity and linkages among factors, and to improve global action. The acquired insights may be the basis for alleviating food insecurity of vulnerable dryland populations.